MANIFESTATION OF RACISM IN BLOOD DIAMOND MOVIE - SAPUTRA, RINOV RAMADHAN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: sociology of literature, racism, white supremacy, mise-en-scene. Humans are social beings existing in different kinds of races. In this context, human beings interact with each other. Unfortunately not all of them can achieve equality because of differences in skin color. The film entitled Blood Diamond points out the racial conflict between Whites people and Black people.The research employs sociological approach in order to serve more detailed focus on the subject being studied. This approach directs the discussion to use racism theory that cover issue : white supremacy. For supporting the approach, this research using facial expression and stereotype to analyze and interpret the data. In this research, there are two problems of the study to be solved, (1) how is racism reflected in Blood Diamond movie, and (2) what are the characteristic of racism in Blood Diamond movie.This research reveals that because of their historical background, Blacks always face discrimination. However, Blood Diamond shows there are some actions from Blacks or Whites. The manifestation of racism in Blood Diamond movie becomes the object of this study. In this film, there are some interaction between Whites people and Blacks people. The researcher notes that there are some spesific racism shown in this movie. The characteristics of racism in this film are shown the superiority of Whites and Blacks. The superiority becomes identity of the Whites people toward black people. However, racism seems to be Whites stereotype toward Blacks. It is shown more clearly in the movie.                                                                                                                           The writer suggests the next researchers to analyze the movie from different perspective using other approach. Psychological approach, for example, This approach can be used to identify the psychological condition of the characters consisting two different races between Blacks and Whiters. It will be interesting to see psychological development of the characters  influenced by racial issues between Blacks and Whites.